2016
DOI: 10.1063/1.4953877
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon generation in sputtered Ga-doped MgZnO thin films for solar cell applications

Abstract: The crystalline, electrical, morphological, optical properties and plasmonic behaviour of Ga doped MgZnO (GMZO) thin films grown at different substrate temperatures (200–600 °C) by a dual ion beam sputtering (DIBS) system are investigated. Transmittance value of more than ∼94% in 400–1000 nm region is observed for all GMZO films. The particle plasmon features can be detected in the absorption coefficient spectra of GMZO grown at 500 and 600 °C in the form of a peak at ∼4.37 eV, which corresponds to a plasmon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…The plasmonic features are clearly observed in the extinction coefficient spectra of both GZO 200 and GZO 300 thin films in the form of the peak at 4.08 and 3.72 eV, respectively, which might correspond to the plasmon resonance peak of the nanoclusters formed in the corresponding thin film. 24 Further, the insets in Figure 3a,b are the corresponding Tauc's plots, which confirm the E g of 3.54 and 3.32 eV for GZO 200 and GZO 300 , respectively. The observed decrement in the value of E g for GZO 300 sample when compared to that of GZO 200 may be due to the metallic clusters formation at the thin film surface.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The plasmonic features are clearly observed in the extinction coefficient spectra of both GZO 200 and GZO 300 thin films in the form of the peak at 4.08 and 3.72 eV, respectively, which might correspond to the plasmon resonance peak of the nanoclusters formed in the corresponding thin film. 24 Further, the insets in Figure 3a,b are the corresponding Tauc's plots, which confirm the E g of 3.54 and 3.32 eV for GZO 200 and GZO 300 , respectively. The observed decrement in the value of E g for GZO 300 sample when compared to that of GZO 200 may be due to the metallic clusters formation at the thin film surface.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…These peaks appear due to the additional absorption in the films, which might have been caused by particle plasmons produced by metal or metal oxide nanoclusters in the GZO 200 and GZO 300 thin films. 24,28,56 The spectral variations in the refractive index (n) and the extinction coefficient (k) of the GZO 200 and GZO 300 films are plotted in Figure 2c,d, acquired from data conversion using the dielectric functions as depicted in Figure 2a,b. The maximum value of n is 2.2 and 3.37 for GZO 200 and GZO 300 , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in the material issues of Mg x Zn 1−x O thin films may lead to applications including MgZnO p-n heterostructure light-emitting devices that operate at 355 nm [14], plasmonic generation in Ga-doped MgZnO for solar cell technologies [15], and solar-blind UV detectors with a cutoff at 270 nm [16]. Additionally, it has been found that the MgZnO thin film transistors at the small Mg composition range Mg 0.06 Zn 0.94 O have better device performance than pure ZnO channel devices [17].…”
Section: Introductionmentioning
confidence: 99%